Fluorine plasma treatment of bare and nitrilotris(methylene)triphosphonic acid (NP) protected aluminum: an XPS and ToF‐SIMS study. (22nd September 2014) - Madaan, Nitesh; Diwan, Anubhav; Linford, Matthew R.
<x xml:space="preserve">Abstract</x> Nitrilotris(methylene)triphosphonic acid (NP) is a technologically important molecule that has been used for years as a corrosion inhibitor and/or adhesion promoter on aluminum and other metal surfaces. However, to the best of our knowledge, the detailed surface characterization of NP adsorbed on aluminum, or on any other surface, has not been reported. Herein, we report an X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) analysis of a series of untreated and NP‐coated aluminum substrates that were exposed to the downstream products of a fluoroalkane + oxygen plasma for different amounts of time (from 0 to 20 s). As indicated by P 2p, N 1s, Al 2p, O 1s, and F 1s narrow scans, even a 4‐s plasma treatment significantly damages the NP protective layer and converts the native aluminum oxide into aluminum oxyfluoride. Heat treatment of the fluorine plasma‐treated samples in the air substantially converts the aluminum oxyfluoride back to aluminum oxide, while similar heating under vacuum results in little change to the materials. A slow loss of fluorine from the samples occurs over the course of weeks when they are stored in the air. A ToF‐SIMS analysis reveals sets of signals that are consistent with no surface treatment, NP treatment, or fluorine plasma treatment. A principal component analysis of the negative ion ToF‐SIMS spectra from the samples shows the expected differentiation of the samples. Copyright © 2014 John Wiley & Sons, Ltd.